Facile preparation of high-quality perovskites for efficient solar cells via a fast conversion of wet PbI2 precursor films. Issue 36 (24th April 2017) - Sun, Chongyang; Guo, Yiping; Fang, Bijun; Guan, Lin; Duan, Huanan; Chen, Yujie; Li, Hua; Liu, Hezhou
Abstract : Facile preparation of high-quality CH3 NH3 PbI3 films with excellent photovoltaic performance by using an annealing-free method and wet PbI2 precursor films. Abstract : High-performance perovskite solar cells are strongly dependent on the quality of the perovskite layer. Here, a high crystallinity, sufficiently smooth and pinhole-free CH3 NH3 PbI3 film with excellent photovoltaic properties has been successfully prepared by a facile and reproducible approach, in which the CH3 NH3 I (MAI) was deposited directly onto wet PbI2 (w-PbI2 ) precursor films. It is found that the outstanding morphology and low crystallization of the w-PbI2 film significantly promotes the conversion of PbI2 to CH3 NH3 PbI3, improves the morphology and crystallinity of the perovskite, and leads to further reduction of the recombination of photogenerated carriers and increment of the lifetimes of charge carriers in the fabricated devices. Compared with the control devices fabricated using a conventional dry and compact PbI2 film, perovskite solar cells fabricated by using this new method show much higher efficiency and reproducibility. The average power conversion efficiency of the fabricated solar cells is greatly improved from 9.76 ± 0.46% to 15.22 ± 0.17%, which is an increase of nearly 56%. Thus, we demonstrate an effective strategy to prepare high-quality perovskite films with excellent photovoltaic properties.